P-037 Death and disability after coil embolization of ruptured and unruptured aneurysms in the Matrix and Platinum Science (MAPS) trial. (4th July 2012) - Nesbit, G; Johnston, S; Gholkar, A; Turk, A; Hetts, S; Mocco, J; Imm, S; Ge, S; McDougall, C
Abstract : Background and Purpose: We sought to evaluate overall rates of disability and mortality in patients treated with coil embolization for unruptured and ruptured intracranial aneurysms who were enrolled in the MAPS trial, a multicenter randomized trial that showed that Matrix2 biocompatible absorbable polymer-coated coils were noninferior to GDC bare-platinum coils. Materials and Methods: We conducted a randomized trial with blinded outcome assessment performed at 43 centers worldwide. Eligible patients were 18–80 years old with a single documented untreated intracranial saccular aneurysm, 4–20 mm, ruptured or unruptured (Hunt and Hess score I-III, modified Rankin Scale (mRS) score 0–3) for which both Matrix2 and GDC coils were treatment options, and for which primary coiling treatment was planned to be completed during a single procedure. mRS was assessed at baseline and 1 year follow-up, and predictors of disability or mortality (mRS>3) and a worsening in the mRS were evaluated in univariate and multivariable models using logistic regression. The trial was registered at http://clinicaltrials.gov as NCT00396981 . Results: Among 626 subjects enrolled, 570 had an mRS assessment available at 1 year, of whom 208 initially presented with a ruptured aneurysm and 362 with an unruptured aneurysm. During 1 year follow-up, 24 had died (3.8%), of which 7 (1.1%) were judged device or procedure related by the clinical events committee; another 11 were disabled (1.8%). Rates of death or disability were greater for ruptured aneurysms (9.6%) than for unruptured aneurysms (4.1%, p=0.009); however, rates of worsening in mRS were similar (ruptured 11.7% vs 10.2%, p=0.583). Rates of death and disability were similar for those randomized to GDC compared to Matrix (p=0.601), as were rates of worsening of mRS (p=0.489). Independent predictors of death or disability were older age (per decade, OR 2.1, 95% CI 1.3 to 3.4, p=0.001), current smoker (OR 5.5, 1.9 to 15.5, p=0.0014), diabetes (OR 4.5, 1.4 to 14.6, p=0.012) and current use of illicit drugs or alcohol (OR 3.5, 1.0 to 11.9, p=0.042). Coil type (GDC vs Matrix), other clinical characteristics, aneurysm characteristics, and retreatment were not predictors of death or disability in univariate or multivariate models. Conclusions: Coil embolization of intracranial aneurysms is rarely associated with death or disability, with overall rates generally lower than previously reported. Although older age and initial rupture are known to be associated with worse outcomes, current smoking status, diabetes, and current use of illicit drugs or alcohol were also baseline predictors but requires independent validation from future studies. Competing interests: G Nesbit: None. S Johnston: Boston Scientific/Stryker Neurovascular. A Gholkar: None. A Turk: None. S Hetts: NIH-NIBIB, Stryker Neurovascular. J Mocco: None. S Imm: Stryker Neurovascular. S Ge: Stryker Neurovascular. C McDougall: None.